Life cycle assessment (LCA) refuse derived fuel (RDF) waste in pusat inovasi agro teknologi (PIAT) Universitas Gadjah Mada as alternative waste management for energy - Titi Tiara Anasstasia; Muhammad Mufti Azis; Imam Haryanto; Rio Arya Pratama (Indonesian Life Cycle Assessment Network (ILCAN), 2018)
Pusat Inovasi Agroteknologi (PIAT) handles institutional waste generated from Universitas Gadjah Mada (UGM). Waste from UGM is called Institutional Solid Waste (ISW) reaches 1,427.27 kg / week. In this study, Life Cycle Assessment (LCA) analysis was used as a tool to calculate and evaluate the environmental impact of potential ISW conversion to densified Refused Derived Fuel (dRDF) with gate to gate framework system. For simulation, OpenLCA software equipped with Ecoinvent database was used in this work. The results showed that conversion of combustible inorganic waste into densified Refuse Derived Fuel (dRDF) along with conversion of organic waste into compost gave following environmental impacts: global warming potential of 1.3E+00 kg CO2 eq, acidification 3.9E-03kg SO4 eq., eutrophication 7.1E-01 kg P eq., human toxicity 1.2E+00 kg 1.4-dichlorobenzene and terrestrial ecotoxicity 6.1E-02 kg 1.4-dichlorobenzene. By separating combustible from non-combustible inorganic waste may significantly improve the quality of dRDF as well as the quantity of compost. The substitution of coal using dRDF combined with the selling of compost is a feasible option. In addition, our results also showed that installation of exhaust gas emission control could further reduce the environmental impact of dRDF production. An economic evaluation was also conducted to evaluate the scenario of converting ISW into dRDF and compost. This option appeared to be profitable, provided that no restrictions to the processed waste, steady flow of dRDF product to the end-users, and the presence of standard price for dRDF.